PEMANFAATAN TEPUNG KACANG TUNGGAK (Vigna unguiculata) DAN TEPUNG BIJI SAGA POHON (Adenanthera pavonina Linn) DALAM PEMBUATAN FLAKES - Iswahyudi Iswahyudi; Yulia Shandy Khoirunissa; Imawati Eka Putri (ARGIPA (Arsip Gizi dan Pangan), 2022)
Cowpea and tree saga seeds are local food ingredients whose utilization is still limited and not widely known by the public. The purpose of this study was to produce flakes based on cowpea flour and tree saga seeds which were chemically and organoleptically acceptable. This study used a completely randomized design (CRD) with one factor and two replications. The treatment factor in this study was the proportion of cowpea flour and tree saga seed flour with various formulation levels, namely F1 (50:15), F2 (45:20) and F3 (40:25). Organoleptic test was carried out using 50 panelists. Chemical analysis carried out included water content, ash content, protein, fat, carbohydrates, energy and calcium in the overall formulation as well as analysis of crude fiber content in the selected formulation. Data analysis was performed using ANOVA and Kruskall Wallis tests. If the p-value <0.05, it was continued with Duncan and Mann Whitney test at 95% significance level. The results showed that the substitution of cowpea flour and saga tree seed flour in making flakes had a significant effect on the level of preference for color, taste and overall as well as the quality of color, taste, aroma, and texture. The results of chemical analysis showed that the substitution of cowpea flour and saga tree seed flour in making flakes had a significant effect on water content, ash content, protein, fat, carbohydrates, energy and calcium. The selected flakes were F1 (50:15) with nutritional content per 100 g of ingredients, namely energy 428.88 kcal, carbohydrates 70.41 g, protein 16.35 g, fat 9.09 g, calcium 173.04 mg and crude fiber 1.04 g.